Tunica vaginalis: An aid in hypospadias fistula repair: Our experience of 14 cases - Yogender Singh Kadian; Kamal Nain Rattan; Jagjit Singh; Mahavir Singh; Pradeep Kajal; Dheeraj Parihar (Wolters Kluwer Medknow Publications, 2011)
Background: Urethrocutaneous fistula is the most common complication of hypospadias surgery. The correction of such fistula is associated with a failure rate of 10 to 40%. The step in successful repair of a fistula is separation of the suture lines in the urethra and skin using well vascularized elastic tissue. We report our experience of using the tunica vaginalis flap as a layer between the neourethra and skin suture line in repair of recurrent urethrocutaneous fistula. Patients and Methods: We have used the tunica vaginalis flap for the repair of recurrent urethrocutaneous fistula in 14 children with a mean age of 6.5 years (range 3-14 years). All patients had undergone previous hypospadias repair and at least one previous attempt to close the fistula had failed. Surgery was initiated by injecting a povidone solution via urethral meatus to identify all fistulae. The fistulae were closed primarily and urethral suture line was covered with a flap of tunica vaginalis which was harvested either through a small scrotal incision and mobilized via a subcutaneous tunnel into the penile shaft (8/14) or by the same incision as for fistula closure (6/14). The testis was fixed to the scrotum. A urethral catheter was kept for urinary diversion for 10 days. Results: The repair was successful in all but one patient in whom there was leak from the fistula site. One patient in whom tunica vaginalis fascia was tunnelled into neourethra developed scrotal haematoma which needed drainage. Penile cosmesis was acceptable without any significant postoperative testicular complication in 13/14 patients. Conclusion: Repair of recurrent urethrocutaneous fistula with a tunica vaginalis flap is highly effective regardless of fistula location. This flap is easy to mobilize and provide effective coverage of urethral suture line. Putting a glove drain should be considered into scrotal wound if perfect haemostasis is doubtful.